SELF-ESTEEM, PERSONALITY TYPES AND SPEAKING PROFICIENCY OF TENTH GRADERS OF ISLAMIC HIGH SCHOOL - Masrifatul Afifah; Ary Setya Budhi Ningrum (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2023)
Self-esteem and personality types are required to accomplish self-quality. Some experts assume that speaking is correlated with self-esteem and personality types. Therefore, the goal of the research is to investigate the correlation between self-esteem, personality types and speaking proficiency. This correlational study involved 129 of tenth graders students of MAN 1 Kediri. To collect data, the instrument used include a closed-ended questionnaire about self-esteem and personality types and a speaking test. There are some findings according to the research problem stated in this research. The first, significant positive correlation between self-esteem and speaking proficiency evidenced by Sig.000<0.05 was found. The second, there was a significant positive correlation between personality types and speaking proficiency evidenced by Sig.000<0.05. The last, there was significant simultaneous positive correlation between self-esteem and personality types with speaking proficiency evidenced by Sig.000<0.05. From those findings, all of the alternative hypothesis (Ha) was accepted, it means that all of the variables examined have positive significant correlation.